2014
DOI: 10.1371/journal.pone.0108994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Kidney Proximal Tubular Glucose Reabsorption Does Not Prevent against Diabetic Nephropathy in Type 1 Diabetic eNOS Knockout Mice

Abstract: Background and ObjectiveSodium glucose cotransporter 2 (SGLT2) is the main luminal glucose transporter in the kidney. SGLT2 inhibition results in glycosuria and improved glycaemic control. Drugs inhibiting this transporter have recently been approved for clinical use and have been suggested to have potential renoprotective benefits by limiting glycotoxicity in the proximal tubule. We aimed to determine the renoprotective benefits of empagliflozin, an SGLT2 inhibitor, independent of its glucose lowering effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 34 publications
4
36
0
1
Order By: Relevance
“…Phlorizin prevented increases in total kidney weight and proteinuria in diabetic rats 31 Empagliflozin attenuated increases in kidney weight, albuminuria, markers of kidney growth and markers of inflammation in diabetic mice 29,34 SGLT2 inhibitors, including luseogliflozin, empagliflozin and tofogliflozin, have shown improved markers of diabetic nephropathy in diabetic rats 32,33 Decreased proteinuria has been observed with SGLT2 inhibition in diabetic rodents 31,35 Canagliflozin provided reductions in ACR 14,16,18,19 Indirect effects SGLT2 inhibitors have been shown to improve parameters associated with reductions in measures of diabetic nephropathy, including hyperglycemia, blood pressure and weight in diabetic rats 7,28,29 SGLT2 inhibitors have been shown to improve parameters associated with reductions in measures of diabetic nephropathy, including hyperglycemia, blood pressure, weight and uric acid levels in diabetes (e.g., hyperkalemia, AEs related to volume depletion, bone fractures, cardiovascular safety). This manuscript summarizes renal data from the pooled, placebo-controlled population, including patients with normal renal function from four placebo-controlled studies of canagliflozin 9,11-13 ; active-controlled studies of canagliflozin as add-on to metformin versus glimepiride and sitagliptin 11,14,18 and as add-on to metformin plus sulfonylurea versus sitagliptin 15 ; and a placebo-controlled study in older adults 17,20 ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phlorizin prevented increases in total kidney weight and proteinuria in diabetic rats 31 Empagliflozin attenuated increases in kidney weight, albuminuria, markers of kidney growth and markers of inflammation in diabetic mice 29,34 SGLT2 inhibitors, including luseogliflozin, empagliflozin and tofogliflozin, have shown improved markers of diabetic nephropathy in diabetic rats 32,33 Decreased proteinuria has been observed with SGLT2 inhibition in diabetic rodents 31,35 Canagliflozin provided reductions in ACR 14,16,18,19 Indirect effects SGLT2 inhibitors have been shown to improve parameters associated with reductions in measures of diabetic nephropathy, including hyperglycemia, blood pressure and weight in diabetic rats 7,28,29 SGLT2 inhibitors have been shown to improve parameters associated with reductions in measures of diabetic nephropathy, including hyperglycemia, blood pressure, weight and uric acid levels in diabetes (e.g., hyperkalemia, AEs related to volume depletion, bone fractures, cardiovascular safety). This manuscript summarizes renal data from the pooled, placebo-controlled population, including patients with normal renal function from four placebo-controlled studies of canagliflozin 9,11-13 ; active-controlled studies of canagliflozin as add-on to metformin versus glimepiride and sitagliptin 11,14,18 and as add-on to metformin plus sulfonylurea versus sitagliptin 15 ; and a placebo-controlled study in older adults 17,20 ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from preclinical and clinical studies has shown that treatment with SGLT2 inhibitors may lead to improvements in markers of diabetic nephropathy, thereby suggesting a potential renoprotective role for this class in patients with diabetes (Table 1) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Specifically, SGLT2 inhibitors may confer renoprotection through direct action on glucose lowering, activation of tubuloglomerular feedback and/or potentially weight loss, through volume normalization, reduced intraglomerular pressure and improved BP control [27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Although lowering of ANP is another mechanism that could mitigate the progression of kidney damage in diabetes, the relationship between ANP and SGLT2 inhibition has not been described to date.…”
Section: Effects Of T2dm and Sglt2 Inhibition On The Kidneymentioning
confidence: 99%
“…As outlined above, data in animal models often differ depending upon the model used. Thus, when streptozotocin-induced diabetic endothelial nitric oxide synthase knockout mice were treated with empagliflozin there was no attenuation of albuminuria (44) or improvement in renal lesions or inflammatory markers (44). In contrast, the beneficial effects of empagliflozin on DN lesions were recently described in normotensive BTBR ob/ob mice, where reductions in glomerular hypertrophy, mesangial matrix expansion, albuminuria, and markers of inflammation were observed (45).…”
Section: Sglt2 Inhibitors: Experimental Datamentioning
confidence: 98%
“…SGLT2 inhibition also reduced blood glucose from 400 to 200 mg/dl in T2DM ob/ob mice; again this was associated with a decrease in renal hypertrophy, albuminuria, and markers of inflammation and mesangial matrix expansion [15]. Furthermore, in T1DM eNOS knockout mice with matched high blood glucose levels across all groups, those with SGLT2 inhibition showed no benefit on glomerulosclerosis, tubular atrophy, or tubulointerstitial fibrosis, whereas those treated with an angiotensin II AT1 receptor antagonist did [44]. Together these studies are consistent with the notion that SGLT2 inhibition can lower early kidney growth and inflammation in the diabetic kidney primarily by lowering blood glucose (Figure 1).…”
Section: Does Sglt2 Inhibition Provide Kidney Protection Beyond Lowermentioning
confidence: 99%